What Can We Learn from (Pseudo)Rapidity Distribution in High Energy Collisions? - Fu-Hu Liu; Tian Tian; Jian-Xin Sun; Bao-Chun Li (Advances in High Energy Physics)
Based on the (pseudo)rapidity distribution of final-state particles produced in proton-proton (pp) collisions at high energy, the probability distributions of momenta, longitudinal momenta, transverse momenta (transverse masses), energies, velocities, longitudinal velocities, transverse velocities, and emission angles of the considered particles are obtained in the framework of a multisource thermal model. The number density distributions of particles in coordinate and momentum spaces and related transverse planes, the particle dispersion plots in longitudinal and transverse coordinate spaces, and the particle dispersion plots in transverse momentum plane at the stage of freeze out in high energy pp collisions are also obtained.